Ytterbium (II) Hydride as a Powerful Multielectron Reductant. Issue 52 (30th July 2021) - Richardson, Georgia M.; Douair, Iskander; Cameron, Scott A.; Maron, Laurent; Anker, Mathew D.
Abstract: A dimeric β‐diketiminato ytterbium(II) hydride affects both the two‐electron aromatization of 1, 3, 5, 7‐cyclooctatetraene (COT) and the more challenging two‐electron reduction of polyaromatic hydrocarbons, including naphthalene (E 0 =−2.60 V). Confirmed by Density Functional Theory calculations, these reactions proceed via consecutive polarized Yb−H/C=C insertion and deprotonation steps to provide the respective ytterbium (II) inverse sandwich complexes and hydrogen gas. These observations highlight the ability of a simple ytterbium(II) hydride to act as a powerful two‐electron reductant at room temperature without the necessity of an external electron to initiate the reaction and avoiding radicaloid intermediates. Abstract : A molecular ytterbium(II) hydride enables the two‐electron aromatization of 1, 3, 5, 7‐cyclooctatetraene to provide an inverse sandwich diytterbium cyclooctatetraenyl derivative and hydrogen gas. This reactivity was extended to the more challenging two‐electron reduction of polyaromatic hydrocarbons, including naphthalene (E 0 =−2.60 V), with retention of metal oxidation state. This reactivity proceeds via consecutive polarized Yb−H/C=C insertion and deprotonation pathways that occurs at the dimeric hydride reagent.